Penggunaan Kata Baku di kalangan Mahasiswa Jurusan Pendidikan Geografi Universitas Negeri Medan - Ridha Suyatmika Nainggolan; Ester Y.F Simamora; Putri Roito Lumbantobing; Frinawaty Lestarina Barus (BADAN PENERBIT STIEPARI PRESS, 2024)
Although its development continues from time to time, especially in Indonesia, the influence of slang on the use of Indonesian is not so obvious. The widespread use of slang in society in general has a positive impact on the identity of the Indonesian nation today and in the future. The presence of slang in Indonesian has unwittingly enriched Indonesia's status as a national language. The method in this research uses a qualitative descriptive approach. Quantitative research is a type of research that provides insight into the use of standardized words and non-standardized words among geography students. This research was attended by geography education students of Stambuk 2022 with representatives from each class. The results of the Google form distributed to 16 student respondents of the Geography Education Study Program Stambuk 2022 Medan State University show that students' understanding of standard and non-standard words is quite high. Because, in the Google form there are 20 words, the standard words are only ten, namely obsolete, ideology, practice, response, risk, change, content, method, and system. Except for these ten words, all of them are non-standard words. From this study, it can be concluded that students' understanding of the use of standard and non-standard words is quite high. Students can distinguish between standard words and non-standard words. However, non-standard words are still used in daily communication on campus. This shows how important it is to emphasize the use of good and correct Indonesian in universities in order to maintain linguistic standards.